2015
DOI: 10.1016/j.childyouth.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The developing relationship between recently placed foster infants and toddlers and their foster carers: Do demographic factors, placement characteristics and biological stress markers matter?

Abstract: The developing relationship between recently placed foster infants and toddlers and their foster carers: Do demographic factors, placement characteristics and biological stress markers matter? Children and Youth Services Review, 58,[219][220][221][222][223][224][225][226].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Vanderfaeillie, Van Holen, Vanschoonlandt, Robberechts, and Stroobants () reported that school‐aged children exhibited more mental health problems when their foster parents experienced high levels of stress and when they used more negative parenting strategies. For preschool children, there was also an association between foster parents’ and children's stress levels as measured with biological markers (Van Andel et al., ). There is, however, no knowledge about the impact of the foster family specifically can have on children's PTSS.…”
mentioning
confidence: 99%
“…Vanderfaeillie, Van Holen, Vanschoonlandt, Robberechts, and Stroobants () reported that school‐aged children exhibited more mental health problems when their foster parents experienced high levels of stress and when they used more negative parenting strategies. For preschool children, there was also an association between foster parents’ and children's stress levels as measured with biological markers (Van Andel et al., ). There is, however, no knowledge about the impact of the foster family specifically can have on children's PTSS.…”
mentioning
confidence: 99%
“…Quite a lot of foster care placements have an unfortunate ending because of a mismatch between foster carer and foster child. This mismatch may arise because of high expectations in idealistic foster carers or a lack of basic knowledge of the “quasi adaptation” that very young foster children may show as a coping strategy (Van Andel et al, 2015). It is important that foster carers learn to observe the child and learn to act in a sensitive way toward the child.…”
Section: Discussionmentioning
confidence: 99%
“…It seems clear that the developing relationship between the foster carer and a young foster child is precarious in many ways. The foster carer may not notice the negative effects on the well-being of the child (Van Andel et al, 2015). The conflicting emotions of the child and the insecurity in the relation with the foster carer may lead to elevated stress levels in the child (Dozier, Manni, Gordon, & Peloso, 2006; Leathers, 2003).…”
Section: Challenges For Foster Carer and Foster Child After Placementmentioning
confidence: 99%
“…A sample item is: 'Child is more of a problem than expected'. Internal consistencies of the NOSI-K have been reported to be high (De Brock et al 1992;Haskett et al 2006), and the NOSI-K has been previously used in studies on foster parents (Maaskant et al 2016;Murray et al 2011;Nilsen 2007;Van Andel et al 2015). In the current study the internal consistency for all three waves was 0.96.…”
Section: Parenting Stressmentioning
confidence: 99%